Indigenous fire practices in Wasur National Park Merauke, South Papua - Budiningsih Kushartati; Ridho Nurrochmat Dodik; Wibowo Agung; Ekayani Meti; Nurfatriani Fitri; Yori Kondolangit Enrico (BIO Web of Conferences)
Indigenous communities worldwide have traditionally employed fire as a land management tool to promote ecological enhancement. However, these practices are increasingly threatened by socio-economic changes, leading to a rise in uncontrolled wildfires. This research seeks to understand the traditional burning practices of the Kanume people utilizing a traditional ecological knowledge framework. A qualitative case study design was employed, with data gathered through in-depth interviews, observation, and document analysis. Participants included customary elders and fire practitioners within the Kanume community. The results reveal that fire is an integral component of the Kanume people's traditional farming, land management, and hunting practices. Shifts in these fire practices related to hunting now contribute to uncontrolled wildfires, resulting in the degradation of essential natural resources. These wildfires stem from both internal community dynamics and external factors. Addressing the challenges inherent in these indigenous fire practices is critical for the sustainable livelihood of the Kanume people and the ecological, socio-cultural, and economic functions of Wasur National Park